IMPLEMENTASI PROGRAM SISTEM MOBILE ELEKTRONIK (SIMOLEK) PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA PEKANBARU - Heslianty Manurung; Harapan Tua RFS (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
In order to improve the quality of licensing services in Pekanbaru City the Pekanbaru City Government through the Investment and Integrated One Stop Service Office, Presents the Electronic Mobile Licensing Service Management Information System (SIMOLEK), an Android-based information system for licensing and non-licensing services in Pekanbaru City. To continue to improve and encourage the community to take care of licensing and non-licensing services and increase economic investment in Pekanbaru City, DPMPTSP Pekanbaru City continues to have a strategic plan, through simplifying the service system and application of information systems in licensing services by trying to provide the best service to the community in terms of licensing. The phenomenon of this problem is that the implementation of the Electronic Mobile System Program (SIMOLEK) has not been maximized by the Pekanbaru City Investment and Integrated Services Office (DPMPTSP) and the lack of understanding and socialization of the community for the Electronic Mobile System (SIMOLEK) program. The purpose of this study was to determine the Implementation of the Electronic Mobile System Program (SIMOLEK) at the Investment Office and the One Stop Integrated Service in Pekanbaru City with a descriptive method, the data collected through observation and interviews. This research was conducted using the theory of Charles O Jones in Siti Erna consisting of Organizing, Interpretation and Application. The results of the study indicate that in the implementation of the SIMOLEK program in the Office of Investment and Integrated Services of One Door Pekanbaru City, it can be concluded that it is less optimal in terms of organizational indicators in the implementor of the lack of field experts and outreach to the community. Globalization of the Digital Era and Community Satisfaction are challenges in implementing the electronic mobile system (SIMOLEK) program at the Pekanbaru City Investment and Integrated Services Office.  Keywords : Implementation, Program, Electronic Mobile System.